2021
DOI: 10.3389/fonc.2021.728224
|View full text |Cite
|
Sign up to set email alerts
|

BI-RADS Reading of Non-Mass Lesions on DCE-MRI and Differential Diagnosis Performed by Radiomics and Deep Learning

Abstract: BackgroundA wide variety of benign and malignant processes can manifest as non-mass enhancement (NME) in breast MRI. Compared to mass lesions, there are no distinct features that can be used for differential diagnosis. The purpose is to use the BI-RADS descriptors and models developed using radiomics and deep learning to distinguish benign from malignant NME lesions.Materials and MethodsA total of 150 patients with 104 malignant and 46 benign NME were analyzed. Three radiologists performed reading for morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Hagiwara et al 135 applied CNN to T1, T2, and proton density maps of the brain to extract features common to multiple sclerosis and neuromyelitis optica spectrum disorder, another demyelinating disease, and used this information to differentiate these 2 disorders, achieving an accuracy of 80%. Some studies showed the superiority of the diagnostic ability of CNN over radiomics based on multiparametric MRI 155–158 . For example, Truhn et al 155 developed both CNN and radiomic models to differentiate benign from malignant breast lesions using multiparametric MRI data of T2-weighted images, as well as precontrast and 4 postcontrast DCE T1-weighted images, with the CNN showing a significantly higher AUC than the radiomic model.…”
Section: Analyzing Multiparametric Mr Imagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hagiwara et al 135 applied CNN to T1, T2, and proton density maps of the brain to extract features common to multiple sclerosis and neuromyelitis optica spectrum disorder, another demyelinating disease, and used this information to differentiate these 2 disorders, achieving an accuracy of 80%. Some studies showed the superiority of the diagnostic ability of CNN over radiomics based on multiparametric MRI 155–158 . For example, Truhn et al 155 developed both CNN and radiomic models to differentiate benign from malignant breast lesions using multiparametric MRI data of T2-weighted images, as well as precontrast and 4 postcontrast DCE T1-weighted images, with the CNN showing a significantly higher AUC than the radiomic model.…”
Section: Analyzing Multiparametric Mr Imagesmentioning
confidence: 99%
“…Multiparametric MRI has also been used for the classification or diagnosis of diseases using deep learning. 135,[150][151][152][153][154][155][156][157][158] Hagiwara et al 135 applied CNN to T1, T2, and proton density maps of the brain to extract features common to multiple sclerosis and neuromyelitis optica spectrum disorder, another demyelinating disease, and used this information to differentiate these 2 disorders, achieving an accuracy of 80%. Some studies showed the superiority of the diagnostic ability of CNN over radiomics based on multiparametric MRI.…”
Section: Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The NME lesion is challenging since it is unique for the MRI lexicon, and its management and follow-up lack standardization. ( Figure 1 ) 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…17 The NME lesion is challenging since it is unique for the MRI lexicon, and its management and follow-up lack standardization. (Figure 1) 18,19 This study aims to report our experience with NME lesions diagnosed by screening MRI referred for MRI-guided biopsies and discuss the management and follow-up of these lesions.…”
Section: Introductionmentioning
confidence: 99%